Obstacles in The Bugis Language Learning Process in Pitu Riawa District, Sidenreng Rappang Regency - Saleh, Firman (Mutiara Intelektual Indonesia Press, 2023)
This research aims to explain the problems in regional language learning in schools. This type of research uses a qualitative descriptive approach in the form of a case study using data collection methods, observation, interviews and distributing questionnaires.The results of the research show that there are learning problems in the teaching and learning process, namely teacher problems, learning equipment problems, curriculum problems, and student problems. Teacher problems, namely teachers who teach not in accordance with their educational background, curriculum problems, namely the absence of a regional language curriculum, learning device problems, namely the absence of adequate learning devices, student problems, namely the emergence of student ideologies that consider the Bugis regional language as a backward subject, and consider regional languages as a frightening specter